When Should We Use Intellectual Property Rights? - Romer, Paul (American Economic Review, 2002)
The economic analysis of property rights proceeds in two steps. The first distinguishes rival from nonrival goods. The second contrasts the welfare effects of property rights for these two types of goods. For rival goods, strong property rights lead to efficient outcomes. For nonrival goods, property rights involve the trade-off formalized by William Nordhaus (1969): Weak property rights lead to under-provision. Strong property rights create monopoly distortions. Recent discussions of copyright protection for recorded music have obscured the underlying economic issues. Interested firms deny that music-sharing will reduce the incentives for firms to release new recordings. Artists and recording companies never acknowledge the efficiency costs of prices that far exceed marginal cost. It is left to economists with no stake in the outcome to clarify these issues. (Full disclosure: I have not consulted for anyone in the Napster case.) The stakes in the battle over the music business are small enough to get lost in rounding